STATUS OF LIBRARY AUTOMATION: A STUDY OF MANAGEMENT EDUCATION INSTITUTES LIBRARIES (International Journal of Food and Nutritional Sciences, 2022)
In the era of information communication technology (ICT) new technique are being used for daily functions of the libraries in higher educational institutions. In the era of ICT, the nature of library activities have been changed drastically, in terms of collection development, providing library services, library administration, etc. The present study focuses on the current status of automation in the management education institution’s libraries and major automated library functions, usage of Internet in various sections of the library.